Clinical efficacy of intravenous chemotherapy alone versus intravenous combined with intraperitoneal chemotherapy for newly diagnosed gastric cancer with malignant ascites - Zhang, Suyun; Feng, Rui; Jiang, Tao; Wang, Xinli; Pan, Zhangchi; Li, Ling; Zhang, Shu; Chen, Qiang; Yang, Sheng (Translational Cancer Research; Vol 6, No 6 (December 28, 2017): Translational Cancer Research, 2017)
Background: To retrospectively evaluate clinical efficacy and adverse reactions of intravenous chemotherapy along vs. intravenous combined with intraperitoneal chemotherapy (IPC) in newly diagnosed gastric cancer (GC) with malignant ascites. Methods: Between September 2010 and September 2015, a total of 33 newly diagnosed GC patients combined with malignant ascites were evaluated, of whom 18 received intravenous chemotherapy alone (the simple group) and 15 received intravenous combined with intraperitoneal chemotherapy (the combination group). The short-term objective efficacy and adverse reactions of all patients were evaluated based on treatment methods and the results of follow-up examinations. Simultaneously, the median survival period and the 12-, 18-, 24-, 30-, 36-, 60-month survival rates were obtained through follow-up with patients to evaluate the long-term efficacy. Results: The patient baseline characteristics were similar in two groups in regard to age, gender, ECOG scores before treatment, number of metastatic sites, pathological grading, clinical stage and therapy history (P>0.05). As to the objective efficacy, the objective response rate (ORR) and disease control rates (DCR) were significantly lower in the simple group compared with those in the combination group (11.11% vs. 40.00%, P>0.05; 44.44% vs. 80.00%, P